What Makes a Woman Become a Serial Killer - Cassady, Morgan S. (My University, 2017)
The offender profile information that surrounds the stereotypical serial killer is that the killer is mostly a Caucasian male suspect in his thirties. Males usually kill strangers, and almost all their victims are females killed by a sexual agenda. Female serial killers have much less information known about their motives and killer profiles. Women serial killers are often considered even more dangerous than male serial killers because they kill the unsuspecting and weak (Kelleher & Kelleher, 1998). A female serial killer almost always kills a close friend or family member, or someone in their own household (Vronsky, 2007). While most people consider the dangers of society to be outside the home, the female murderess is even more frightening because she hunts for victims within her own home. A group of 58 previously-researched female serial killers were examined following certain variables as discussed in the gender-responsive literature. The risk assessment of these women was examined to see if their actions did in fact follow the pathways of deviance outlined in the gender-responsive approach to deviance and recidivism. While there is not a specified sequence in which these events must occur, they all are a culmination of what shapes the woman’s probability to lead a life of criminality. The more variables experienced in a woman’s life, the greater her chances are of choosing criminal activity in her lifetime This study found that a woman who experiences a very tumultuous life with abuse, divorce, homelessness, and poverty will have an increased likelihood of inclusion in crime and deviance.
Chapter I: Introduction.1 | Defining A Serial Killer 1 | Summary.2 | Chapter Ii: Review Of Literature4 | Initiation5 | Preferred Methods.6 | Women Who Know Their Victims.6 | Women Who Kill Strangers8 | Detection And Evasion Of Capture.9 | Theoretical Background10 | Gender Differences.11 | The Pathways Perspective.12 | Relationships.13 | Abuse.15 | Mental Illness And Substance Abuse.17 | Poverty.17 | Chapter Iii: Methodology.19 | Overview .19 | Sample20 | Variables.20 | Data Analysis Plan.21 | Codebook Formulation.22 | Data Collection.23 | Chapter Iv: Results .25 | Childhood Demographics25 | Adult Factors.26 | The Crimes28 | Killer Demographics.30 | Discussion.32 | Methods Of Murder.32 | Career Length33 | Gender-responsive Variables.33 | Traumatic Events.34 | Abuse.34 | Relationships.35 | Poverty35 | Homelessness, Prostitution, And Drug Abuse.35 | Mental Illness36 | Interacting Factors.37 | Chapter V: Conclusion.39 | Study Limitations40 | Similar/different Findings41 | Policy Implications.43 | References46 | Appendix A: Codebook.50 | Appendix B: Females In Study, State, And Newspaper Publication 56 | Appendix C: Institutional Review Board Exemption Form59 |
Keywords: Serial murderers; Serial murderers--Women; Murder; Gender; Gender identity in literature